2000
DOI: 10.1159/000007746
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Monitoring of Nitric Oxide Release Induced by Cholecystokinin from the Choledochal Sphincter in Guinea Pigs

Abstract: Background/Aims: Many in vitro studies in the choledochoduodenal junction of the guinea pig have shown that cholecystokinin (CCK) contracts the sphincter of Oddi (SO). This study, using the choledochal sphincter of the guinea pig as the SO, evaluates the hypothesis that effects of CCK on the SO were mediated by nitric oxide (NO). Methods: Spontaneous motility and effects of CCK on the choledochal sphincter were recorded using a constant-perfusion technique, and direct measurement of NO release using a specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Other functional studies have demonstrated that the SO produces detectable NO and that NO mediates the relaxatory effect of CCK-8 in the guinea pig SO longitudinal muscle [35]. Furthermore, intravenous administration of the NO scavenger, diaspirin cross-linked hemoglobin (DCLHb), reduced SO trans-sphincteric flow [36].…”
Section: Neurotransmittersmentioning
confidence: 99%
“…Other functional studies have demonstrated that the SO produces detectable NO and that NO mediates the relaxatory effect of CCK-8 in the guinea pig SO longitudinal muscle [35]. Furthermore, intravenous administration of the NO scavenger, diaspirin cross-linked hemoglobin (DCLHb), reduced SO trans-sphincteric flow [36].…”
Section: Neurotransmittersmentioning
confidence: 99%